2020
DOI: 10.3390/catal10020163
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Experimental Study of CO2 Conversion into Methanol by Synthesized Photocatalyst (ZnFe2O4/TiO2) Using Visible Light as an Energy Source

Abstract: Ozone layer depletion is a serious threat due to the extensive release of greenhouse gases. The emission of carbon dioxide (CO2) from fossil fuel combustion is a major reason for global warming. Energy demands and climate change are coupled with each other. CO2is a major gas contributing to global warming; hence, the conversion of CO2 into useful products such as methanol, formic acid, formaldehyde, etc., under visible light is an attractive topic. Challenges associated with the current research include synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…%. Manzoor et al [48] reported a decrease in band gap after the combination of ZnFe 2 O 4 with TiO 2 with a proper 1:1 ratio. As matter of fact, this ratio leads to an effective narrowing of the bandgap and maximum absorption of the visible light.…”
Section: Resultsmentioning
confidence: 99%
“…%. Manzoor et al [48] reported a decrease in band gap after the combination of ZnFe 2 O 4 with TiO 2 with a proper 1:1 ratio. As matter of fact, this ratio leads to an effective narrowing of the bandgap and maximum absorption of the visible light.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the MgS-TiO 2 photocatalyst showed maximum yield of 229.1 µmol/g•h of methanol, which is higher than the other reported catalyst. However, the formation of other products, such as formaldehyde, formic acid, as well as backward reaction, still limit the maximum achievable methanol yield [37].…”
Section: Comparison With Previous Studymentioning
confidence: 99%
“…As the most practical application for this class of composite photocatalytic activities such as water pollution degradation [10][11][12][13], CO2 reduction [14], photoelectrochemical (PEC) water splitting and hydrogen production [5,15,16] and PEC oxidation of water [17] have become topics of interest as well as biotechnology and nanomedicine [18][19][20][21][22][23] applications. *Address correspondence to this author at the Department of Physics, Faculty of Shahr-e-Qods branch, Islamic Azad University, P.O.…”
Section: Introductionmentioning
confidence: 99%